Islamic Educational Institution Management in Improving Gr aduate Quality: A Comparative Literature Review - Budi Santoso; Siti Rahmawati (PT. Berkah Smart Academica, 2024)
This comparative literature review examines the management practices of Islamic educational institutions and their impact on graduate quality. The study synthesizes existing research to identify key management strategies, pedagogical approaches, and challenges faced by these institutions. The review analyzes literature from diverse geographical contexts, focusing on curriculum development, teacher training, leadership styles, and the integration of technology. The methodology involves a systematic analysis of scholarly articles, books, and reports. The findings reveal that effective management in Islamic educational institutions involves a balance of traditional Islamic values and modern educational practices. Key elements include strong leadership, a focus on teacher development, integration of technology, and a curriculum that emphasizes both religious and secular knowledge. The review highlights the importance of context-specific approaches, considering the diverse cultural and socio-political environments in which these institutions operate. The conclusion emphasizes the need for ongoing research and adaptation to ensure the continued improvement of graduate quality in Islamic educational institutions, offering insights for educators, policymakers, and researchers.